Coal gangue activating and calcining method

By adding sodium hydroxide and additives to the coal gangue for one-step calcination method and soaking in sulfuric acid, the problem of complex and low efficiency of coal gangue activation in the prior art is solved, and the activation effect and concrete strength of coal gangue are improved.

CN119320250APending Publication Date: 2025-01-17YANGTZE NORMAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411447224.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing coal gangue activation methods are complex and inefficient, so natural coal gangue cannot be used directly in concrete, resulting in a decrease in concrete strength.

Method used

By adding sodium hydroxide and additives to the pretreated coal gangue, performing one-step calcination method to generate coal gangue clinker and immerse it in sulfuric acid, optimizing the pore size distribution and surface area, and forming a disordered network structure to improve the activation effect .

Benefits of technology

It realizes efficient activation of coal gangue, improves its strength and water resistance in concrete, enhances adsorption performance, and simplifies the activation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005088047010000101
    Figure BDA0005088047010000101
Patent Text Reader

Abstract

The invention relates to the technical field of coal gangue activation, in particular to a coal gangue activating and calcining method which comprises the following steps: pretreating coal gangue, adding a sodium hydroxide solution and an auxiliary agent into the pretreated coal gangue, and mixing and stirring to obtain a mixture; calcining the mixture to obtain coal gangue clinker; according to the method, the dispersity of the coal gangue is improved through treatment of the auxiliary and sodium hydroxide, agglomeration among particles is avoided, sodium hydroxide reacts with SiO2 in the coal gangue to generate sodium silicate, the chemical activation process is initiated, and then through calcination and acid leaching, the coal gangue can be effectively activated. Active sites of the coal gangue are increased, the surface property of the coal gangue is changed, an aluminate hydration product with a gelling effect is generated in the calcining process, and the activation effect of the coal gangue is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal gangue activation, and in particular to a coal gangue activation calcination method. Background Art

[0002] Gangue is a kind of black-gray rock with low carbon content and harder than coal that is associated with coal seams during the coal formation process. It is generally produced in the production process of coal mining and excavation. Gangue includes a variety of minerals: kaolin, quartz, montmorillonite, chlorite, etc., among which kaolinite is the main mineral component. Since gangue contains a large amount of minerals, it can be developed and utilized as a resource to achieve the recycling of solid waste and alleviate the shortage of energy. The existing method of recycling gangue is generally to use gangue as a building material, that is, to add gangue to cement, while reducing the amount of cement to ensure the performance of concrete unchanged, and activate gangue for building materials, which can not only solve the problem of recycling gangue, but also bring good economic news. It is an important direction for the comprehensive utilization of gangue, but the activity of natural gangue is very low. Directly mixing natural gangue with cement will lead to a decrease in the strength of concrete. Therefore, natural gangue cannot be used directly.

[0003] Since the activity of coal gangue is low, the first step in recycling coal gangue is to stimulate the activity of coal gangue. At present, the methods for improving the activity of coal gangue are mainly thermal activation, mechanical activation, chemical activation and composite activation. Patent No. CN113045227A discloses a coal gangue activation calcination method, which includes the following steps: grinding coal gangue and calcium-containing substances to obtain a coal gangue mixture, screening the coal gangue mixture, and taking the coal gangue mixture under the screen; sending the coal gangue mixture under the screen into a pelletizing machine, adding water and stirring and mixing evenly, and then making balls to obtain a mixture sphere; continuously putting the mixture sphere into a calcining kiln furnace, igniting the mixture sphere, and calcining and activating at 800-1150°C and an oxidizing environment until the surface of the mixture sphere is black-gray. However, the existing coal gangue activation method requires multiple steps to complete the activation, the activation process is complicated, and the activation efficiency is low. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a method for activating and calcining coal gangue. The present invention adds sodium hydroxide and an auxiliary agent to the pretreated coal gangue, then calcines to obtain coal gangue clinker, acid-leaches the coal gangue clinker, and realizes efficient activation of the coal gangue through a one-step calcination method.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A method for activating and calcining coal gangue comprises the following steps:

[0007] The gangue is pretreated, sodium hydroxide and an auxiliary agent are added to the pretreated gangue, mixed and stirred to obtain a mixture; the mixture is calcined to obtain gangue clinker.

[0008] The gangue clinker is immersed in sulfuric acid for reaction to obtain activated gangue.

[0009] The main components of coal gangue are Al2O3 and SiO2. After adding sodium hydroxide and additives to the coal gangue, the addition of additives can reduce the interaction between coal gangue particles, improve dispersibility, avoid agglomeration between particles, and thus reduce the particle size. SiO2 in the coal gangue reacts with sodium hydroxide to form sodium silicate, which is the main component of water glass. During the calcination process, a chemical activation reaction occurs, providing a strong polar environment, destroying the Si-O bonds and Al-O bonds on the surface of the coal gangue. The addition of sodium hydroxide in the raw materials and the presence of the generated water glass can promote the reaction between the coal gangue and the cement hydration products to form a disordered network structure, thereby improving the strength and water resistance of the coal gangue.

[0010] After calcination, gangue clinker is obtained. During the calcination process, the aluminum oxide in the gangue reacts with sodium hydroxide to form sodium aluminate. The calcined gangue clinker contains sodium aluminate, which reacts with sulfuric acid to form sodium sulfate and aluminate hydration products. The aluminate hydration products with gelling effect are continuously intertwined and polymerized to produce a disordered network structure. In this network structure, Al 3+ Replace Si 4+ And occupy the position of silicon ions, forming [SiO4] connected by oxygen atoms 4- and [AlO4] 5- Structure. Since aluminum ions are trivalent ions, they carry negative charges around them. In order to balance the charge, positively charged alkali ions such as sodium and potassium are attracted to the channels of the gel and exchanged with other ions, so as not to cause structural damage due to the loss of alkali ions. The calcined gangue clinker is immersed in sulfuric acid, and the acidic metal ions such as Al, Fe, and Ca in the gangue are dissolved by acid leaching. This process not only optimizes the pore size distribution and the number of pores inside the gangue, but also increases its specific surface area, thereby improving the adsorption performance of the gangue. In addition, acid modification can also increase the active sites of the gangue, making its adsorption performance stronger. This is because the acid leaching treatment can dissolve certain components in the gangue while retaining or generating new surface functional groups. These functional groups can exchange or chemically react with ions in the solution, thereby changing the surface properties of the gangue and improving the activation effect of the gangue.

[0011] SiO2+2NaOH=Na2SiO3+H2O

[0012] Al2O3+2NaOH=2NaAlO2+H2O

[0013] NaAlO2+H2SO4=Na2SO4+Al(SO4)3+2H2O

[0014] In a preferred embodiment of the present invention, the auxiliary agent is polyethylene glycol or hexadecyltrimethylammonium bromide.

[0015] In a preferred embodiment of the present invention, the usage ratio of coal gangue to sodium hydroxide and auxiliary agent is 400g-600g:15mL-35mL:40g-60g.

[0016] In a preferred embodiment of the present invention, the calcination temperature is 450° C. to 750° C., and the calcination time is 60 min to 120 min.

[0017] In a preferred embodiment of the present invention, the calcination heating rate is 3° C. / min to 4° C. / min.

[0018] In a preferred embodiment of the present invention, the reaction time of the gangue clinker being immersed in sulfuric acid is 2 hours to 3 hours.

[0019] In a preferred embodiment of the present invention, the stirring speed is 120 rpm to 150 rpm, and the stirring time is 3 hours to 5 hours.

[0020] In a preferred embodiment of the present invention, the mass fraction of the sodium hydroxide solution is 35% to 40%, and the mass fraction of the sulfuric acid is 1.84 g / mL.

[0021] In a preferred embodiment of the present invention, the pretreatment method of the coal gangue is to crush the coal gangue and pass it through a 20-40 mesh sieve, and then perform a drying treatment.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention adds sodium hydroxide and an auxiliary agent to the pretreated gangue, mixes and stirs to obtain a mixture; calcines the mixture to obtain gangue clinker; immerses the gangue clinker in sulfuric acid, and realizes efficient activation of the gangue by a one-step calcination method. The main components of gangue are Al2O3 and SiO2. After adding sodium hydroxide and an auxiliary agent to the gangue, the addition of the auxiliary agent reduces the interaction between the gangue particles, improves the dispersibility, avoids the agglomeration between the particles, and then reduces the particle size. The SiO2 in the gangue reacts with sodium hydroxide to form sodium silicate, which is the main component of water glass. During the calcination process, a chemical activation reaction occurs, providing a strong polar environment, destroying the Si-O bond and Al-O bond on the surface of the gangue, and the addition of sodium hydroxide in the raw material and the presence of the generated water glass can promote the reaction between the gangue and the cement hydration product to form a disordered network structure, thereby improving the strength and water resistance of the gangue. After calcination, gangue clinker is obtained. During the calcination process, the aluminum oxide in the gangue reacts with sodium hydroxide to form sodium aluminate. The calcined gangue clinker contains sodium aluminate, which reacts with sulfuric acid to form sodium sulfate and aluminate hydration products. The aluminate hydration products with gelling effect are continuously intertwined and polymerized to produce a disordered network structure. In this network structure, Al 3+ Replace Si 4+ And occupy the position of silicon ions, forming [SiO4] connected by oxygen atoms 4- and [AlO4] 5- Structure. Since aluminum ions are trivalent ions, they carry negative charges around them. In order to balance the charge, positively charged alkali ions such as sodium and potassium are attracted to the channels of the gel and exchanged with other ions, so as not to cause structural damage due to the loss of alkali ions. The calcined gangue clinker is immersed in sulfuric acid, and the acidic metal ions such as Al, Fe, and Ca in the gangue are dissolved by acid leaching. This process not only optimizes the pore size distribution and the number of pores inside the gangue, but also increases its specific surface area, thereby improving the adsorption performance of the gangue. In addition, acid modification can also increase the active sites of the gangue, making its adsorption performance stronger. This is because the acid leaching treatment can dissolve certain components in the gangue while retaining or generating new surface functional groups. These functional groups can exchange or chemically react with ions in the solution, thereby changing the surface properties of the gangue. Improve the activation effect of the gangue.

[0024] SiO2+2NaOH=Na2SiO3+H2O

[0025] Al2O3+2NaOH=2NaAlO2+H2O

[0026] NaAlO2+H2SO4=Na2SO4+Al(SO4)3+2H2O

[0027] 2. The amount of sodium hydroxide added in the present invention also has a certain influence on the activation of coal gangue. When the amount of sodium hydroxide added is too small, it is insufficient for hydration reaction to occur, resulting in insufficient activation. When the sodium hydroxide is within an appropriate range, as the amount of alkali added increases, the hydration reaction rate accelerates, the gel content increases accordingly, and the activation effect increases. However, when the amount of sodium hydroxide added is too much, due to the excessively fast excitation rate, a protective film of hydration products is formed on the surface of the coal gangue particles, preventing the reaction from proceeding further. DETAILED DESCRIPTION

[0028] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with preferred embodiments and data. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0030] Example 1

[0031] A method for activating and calcining coal gangue comprises the following steps:

[0032] (1) Rinse the gangue with water to remove impurities such as soil, then crush it with a hammer, put it into a jaw crusher, pass it through a 30-mesh sieve, and then put it into a drying oven at 100 degrees Celsius for 12 hours for use.

[0033] (2) adding sodium hydroxide and polyethylene glycol additive to the coal gangue pretreated in step (1), wherein the amount ratio of coal gangue, sodium hydroxide solution and polyethylene glycol additive is 500 g:35 mL:50 g, mixing and stirring, the stirring speed is 130 rpm, and the stirring time is 4 hours to obtain a mixture.

[0034] (3) calcining the mixture at 600° C. for 120 min to obtain coal gangue clinker.

[0035] (4) The gangue clinker is immersed in sulfuric acid with a concentration of 1.84 g / L and reacted for 2.5 hours to obtain activated gangue.

[0036] Example 2

[0037] A method for activating and calcining coal gangue comprises the following steps:

[0038] (1) Rinse the gangue with water to remove impurities such as soil, then crush it with a hammer, put it into a jaw crusher, pass it through a 20-mesh sieve, and then put it into a drying oven at 100 degrees Celsius for 12 hours for use.

[0039] (2) adding sodium hydroxide and polyethylene glycol additive to the coal gangue pretreated in step (1), wherein the amount ratio of coal gangue, sodium hydroxide solution and polyethylene glycol additive is 400 g:15 mL:40 g, mixing and stirring, the stirring speed is 120 rpm, and the stirring time is 5 hours to obtain a mixture.

[0040] (3) calcining the mixture at 450° C. for 100 min to obtain coal gangue clinker.

[0041] (4) The gangue clinker is immersed in sulfuric acid with a concentration of 1.84 g / L and reacted for 2 hours to obtain activated gangue.

[0042] Example 3

[0043] A method for activating and calcining coal gangue comprises the following steps:

[0044] (1) Rinse the gangue with water to remove impurities such as soil, then crush it with a hammer, put it into a jaw crusher, pass it through a 40-mesh sieve, and then put it into a drying oven at 100 degrees Celsius for 12 hours for use.

[0045] (2) adding sodium hydroxide and polyethylene glycol additive to the coal gangue pretreated in step (1), wherein the amount ratio of coal gangue, sodium hydroxide solution and polyethylene glycol additive is 600 g:20 mL:60 g, mixing and stirring, the stirring speed is 150 rpm, and the stirring time is 3 hours to obtain a mixture.

[0046] (3) calcining the mixture at 750° C. for 60 min to obtain coal gangue clinker.

[0047] (4) The gangue clinker is immersed in sulfuric acid with a concentration of 1.84 g / L and reacted for 3 hours to obtain activated gangue.

[0048] Comparative Example 1

[0049] A method for activating and calcining coal gangue comprises the following steps:

[0050] (1) The gangue is washed with water to remove impurities such as soil, then crushed with a hammer, and then placed in a jaw crusher. After crushing, it is sieved through a 40-mesh sieve and then placed in a drying oven at 100 degrees Celsius for 12 hours for use.

[0051] (2) adding sodium hydroxide to the coal gangue pretreated in step (1), wherein the amount ratio of the coal gangue to the sodium hydroxide solution is 500 g:20 mL, mixing and stirring at a stirring speed of 130 rpm for 4 hours to obtain a mixture.

[0052] (3) calcining the mixture at 600° C. for 120 min to obtain coal gangue clinker.

[0053] (4) The gangue clinker is immersed in sulfuric acid with a concentration of 1.84 g / L and reacted for 2.5 hours to obtain activated gangue.

[0054] Comparative Example 2

[0055] A method for activating and calcining coal gangue comprises the following steps:

[0056] (1) Rinse the gangue with water to remove impurities such as soil, then crush it with a hammer, put it into a jaw crusher, pass it through a 30-mesh sieve, and then put it into a drying oven at 100 degrees Celsius for 12 hours for use.

[0057] (2) Adding polyethylene glycol additive to the coal gangue pretreated in step (1), wherein the amount ratio of coal gangue to polyethylene glycol additive is 500g:50g, mixing and stirring, the stirring speed is 130rmp, and the stirring time is 4 hours to obtain a mixture.

[0058] (3) calcining the mixture at 600° C. for 120 min to obtain coal gangue clinker.

[0059] (4) The gangue clinker is immersed in sulfuric acid with a concentration of 1.84 g / L and reacted for 2.5 hours to obtain activated gangue.

[0060] Comparative Example 3

[0061] A method for activating and calcining coal gangue comprises the following steps:

[0062] (1) Rinse the gangue with water to remove impurities such as soil, then crush it with a hammer, put it into a jaw crusher, pass it through a 30-mesh sieve, and then put it into a drying oven at 100 degrees Celsius for 12 hours for use.

[0063] (2) adding sodium hydroxide and polyethylene glycol additive to the coal gangue pretreated in step (1), wherein the amount ratio of coal gangue, sodium hydroxide solution and polyethylene glycol additive is 500 g:20 mL:50 g, mixing and stirring, the stirring speed is 130 rpm, and the stirring time is 4 hours to obtain a mixture.

[0064] (3) calcining the mixture at 600° C. for 120 min to obtain activated coal gangue.

[0065] Comparative Example 4

[0066] A method for activating and calcining coal gangue comprises the following steps:

[0067] (1) Wash the gangue with water to remove impurities such as soil, then crush it with a hammer, put it into a jaw crusher, pass it through a 30-mesh sieve after crushing, and then put it into a drying oven at 100 degrees Celsius for 12 hours for standby use;

[0068] (2) adding sodium hydroxide and polyethylene glycol to the pretreated coal gangue in step (1), wherein the ratio of coal gangue, sodium hydroxide solution and polyethylene glycol is 500 g:40 mL:50 g, mixing and stirring at a stirring speed of 130 rpm for 4 hours to obtain a mixture;

[0069] (3) calcining the mixture at 600° C. for 120 min to obtain coal gangue clinker;

[0070] (4) The gangue clinker is immersed in sulfuric acid with a concentration of 1.84 g / L and reacted for 2.5 hours to obtain activated gangue.

[0071] Comparative Example 5

[0072] A method for activating and calcining coal gangue comprises the following steps:

[0073] (1) Wash the gangue with water to remove impurities such as soil, then crush it with a hammer, put it into a jaw crusher, pass it through a 30-mesh sieve after crushing, and then put it into a drying oven at 100 degrees Celsius for 12 hours for standby use;

[0074] (2) adding sodium hydroxide and polyethylene glycol to the coal gangue pretreated in step (1), wherein the ratio of coal gangue, sodium hydroxide solution and polyethylene glycol is 500 g:10 mL:50 g, mixing and stirring at a stirring speed of 130 rpm for 4 hours to obtain a mixture;

[0075] (3) calcining the mixture at 600° C. for 120 min to obtain coal gangue clinker;

[0076] (4) The gangue clinker is immersed in sulfuric acid with a concentration of 1.84 g / L and reacted for 2.5 hours to obtain activated gangue.

[0077] Application Example 1

[0078] The activated coal gangue prepared in Example 1 replaced 20% of the cement, and concrete specimens were prepared according to a mass ratio of cementitious material to standard sand of 1:3 and a water-cement ratio of 0.45. The prepared specimens were placed in a standard constant humidity and constant temperature curing box with a temperature of 18°C ​​to 22°C and a humidity of >90% using a standard curing method and cured to the corresponding ages of 7d, 14d and 28d, and the compressive strength was tested respectively.

[0079] Application Example 2

[0080] The activated coal gangue prepared in Example 2 replaced 20% of the cement, and concrete specimens were prepared according to the mass ratio of cementitious material to standard sand of 1:3 and the water-cement ratio of 0.45. The prepared specimens were placed in a standard constant humidity and constant temperature curing box with a temperature of 18°C ​​to 22°C and a humidity of >90% using the standard curing method and cured to the corresponding ages of 7d, 14d and 28d, and the compressive strength was tested respectively.

[0081] Application Comparative Example 1

[0082] The activated coal gangue obtained in Comparative Example 1 was used to replace 20% of the cement, and concrete specimens were prepared according to the mass ratio of cementitious material to standard sand of 1:3 and the water-cement ratio of 0.45. The prepared specimens were placed in a standard constant humidity and constant temperature curing box with a temperature of 18°C ​​to 22°C and a humidity of >90% using the standard curing method and cured to the corresponding ages of 7d, 14d and 28d, and the compressive strength was tested respectively.

[0083] Application Comparative Example 2

[0084] The activated coal gangue obtained in Comparative Example 2 was used to replace 20% of the cement, and concrete specimens were prepared according to the mass ratio of cementitious material to standard sand of 1:3 and the water-cement ratio of 0.45. The prepared specimens were placed in a standard constant humidity and constant temperature curing box with a temperature of 18°C ​​to 22°C and a humidity of >90% using the standard curing method and cured to the corresponding ages of 7d, 14d and 28d, and the compressive strength was tested respectively.

[0085] Application Comparative Example 3

[0086] The activated coal gangue obtained in Comparative Example 3 was used to replace 20% of the cement, and concrete specimens were prepared according to the mass ratio of cementitious material to standard sand of 1:3 and the water-cement ratio of 0.45. The prepared specimens were placed in a standard constant humidity and constant temperature curing box with a temperature of 18°C ​​to 22°C and a humidity of >90% using the standard curing method and cured to the corresponding ages of 7d, 14d and 28d, and the compressive strength was tested respectively.

[0087] Application Comparative Example 4

[0088] The activated coal gangue obtained in Comparative Example 4 was used to replace 20% of the cement, and concrete specimens were prepared according to the mass ratio of cementitious material to standard sand of 1:3 and the water-cement ratio of 0.45. The prepared specimens were placed in a standard constant humidity and constant temperature curing box with a temperature of 18°C ​​to 22°C and a humidity of >90% using the standard curing method and cured to the corresponding ages of 7d, 14d and 28d, and the compressive strength was tested respectively.

[0089] Application Comparative Example 5

[0090] The activated coal gangue obtained in Comparative Example 5 was used to replace 20% of the cement, and concrete specimens were prepared according to the mass ratio of cementitious material to standard sand of 1:3 and the water-cement ratio of 0.45. The prepared specimens were placed in a standard constant humidity and constant temperature curing box with a temperature of 18°C ​​to 22°C and a humidity of >90% using the standard curing method and cured to the corresponding ages of 7d, 14d and 28d, and the compressive strength was tested respectively.

[0091] Performance Testing

[0092] The activated coal gangue prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was added to the Portland cement clinker, mixed evenly and formed in a 30cm*30cm*30cm slurry test mold, and the initial setting time and the compressive strength after curing for different days were tested. The test results are shown in Table 1.

[0093] Table 1 Test results of concrete specimens prepared by application examples 1 to 3 and application comparative examples 1 to 5

[0094]

[0095] From the results in Table 1, it can be seen that the compressive strength of the concrete specimens prepared by Application Examples 1 to 3 of the present invention after curing for 7d, 14d and 28d is greatly improved, meeting the 42.5 cement strength requirement, and the compressive strength of the concrete specimens of Application Examples 1 to 3 is significantly better than that of Application Comparative Examples 1 to 5. In addition, the initial setting time of the concrete specimens of Application Examples 1 to 3 of the present invention is significantly shorter than that of Application Comparative Examples 1 to 5, indicating that the gangue treated by the method of the present invention has good activation performance, and can be used as a cementitious material for cement concrete to improve the compressive strength and shorten the initial setting time. In Comparative Example 1, since no additives are added, the gangue particles interact with each other, resulting in a high degree of aggregation, and the particles are easy to Agglomeration occurs, which affects the activation effect of the coal gangue. In Comparative Example 2, since no sodium hydroxide is added, sodium silicate cannot be generated, chemical activation cannot be initiated, and a disordered network structure cannot be formed. The effect of improving the strength and water resistance of the coal gangue is not good. In Comparative Example 3, since no acid leaching is performed, there are fewer active sites on the surface of the coal gangue, and the formation of hydration products such as sodium sulfate and aluminate cannot be promoted, and the activation effect of the coal gangue is reduced. In Comparative Example 4, due to the high content of sodium hydroxide added and the excessively fast excitation rate, a layer of hydration product protective film is formed on the surface of the coal gangue particles, preventing the reaction from proceeding further. In Comparative Example 5, due to the low content of sodium hydroxide added, the activation of the coal gangue is insufficient. Therefore, the compressive strength of the concrete specimens prepared using Comparative Examples 1 to 5 is reduced, and the initial setting time is prolonged.

[0096] In summary, the present invention adds sodium hydroxide and an auxiliary agent to the pretreated coal gangue, mixes and stirs to obtain a mixture; calcines the mixture to obtain coal gangue clinker; and immerses the coal gangue clinker in sulfuric acid for reaction to obtain activated coal gangue. The main components of coal gangue are Al2O3 and SiO2. After adding sodium hydroxide and an auxiliary agent to the coal gangue, the addition of the auxiliary agent reduces the interaction between the coal gangue particles, improves the dispersibility, avoids the agglomeration between the particles, and then reduces the particle size. The SiO2 in the coal gangue reacts with sodium hydroxide to form sodium silicate, which is the main component of water glass. During the calcination process, a chemical activation reaction occurs, providing a strong polar environment, destroying the Si-O bond and Al-O bond on the surface of the coal gangue, and the addition of sodium hydroxide in the raw material and the presence of the generated water glass can promote the reaction between the coal gangue and the cement hydration product to form a disordered network structure, thereby improving the strength and water resistance of the coal gangue. After calcination, gangue clinker is obtained. During the calcination process, the aluminum oxide in the gangue reacts with sodium hydroxide to form sodium aluminate. The calcined gangue clinker contains sodium aluminate, which reacts with sulfuric acid to form sodium sulfate and aluminate hydration products. The aluminate hydration products with gelling effect are continuously intertwined and polymerized to produce a disordered network structure. In this network structure, Al3+ Replace Si 4+ The silicon ions are occupied, forming [SiO4] connected by oxygen atoms. 4- and [AlO4] 5- Structure. Since aluminum ions are trivalent ions, they carry negative charges around them. In order to balance the charge, positively charged alkali ions such as sodium and potassium are attracted to the channels of the gel and exchanged with other ions, so as not to cause structural damage due to the loss of alkali ions. The calcined gangue clinker is put into sulfuric acid, and the acidic metal ions such as Al, Fe, and Ca in the gangue are dissolved by acid leaching. This process not only optimizes the pore size distribution and the number of pores inside the gangue, but also increases its specific surface area, thereby improving the adsorption performance of the gangue. In addition, acid modification can also increase the active sites of the gangue, making its adsorption performance stronger. This is because the acid leaching treatment can dissolve certain components in the gangue, while retaining or generating new surface functional groups, which can exchange or chemically react with ions in the solution, thereby changing the surface properties of the gangue. Improve the activation effect of the gangue.

[0097] It should be noted that when the present invention relates to a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundant description, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments. Therefore, the attached protection scope is intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the present invention.

[0098] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the protection scope of the present invention and its equivalent technology, the present invention is also intended to include these modifications and variations.

Claims

1. A method for activating and calcining coal gangue, characterized in that: The following steps are involved: Pre-treating the coal gangue, adding sodium hydroxide solution and an auxiliary agent to the pre-treated coal gangue, mixing and stirring to obtain a mixture; calcining the mixture to obtain gangue clinker; The gangue clinker is immersed in sulfuric acid for reaction to obtain activated gangue.

2. The method for activated calcination of coal gangue according to claim 1, characterized in that: The auxiliary agent is polyethylene glycol or hexadecyltrimethylammonium bromide.

3. The method for activated calcination of coal gangue according to claim 1, characterized in that: The dosage ratio of coal gangue to sodium hydroxide and auxiliary agent is 400g-600g:15mL-35mL:40g-60g.

4. The method for activated calcination of coal gangue according to claim 1, characterized in that: The calcination temperature is 450°C to 750°C, and the calcination time is 60min to 120min.

5. The method for activated calcination of coal gangue according to claim 1, characterized in that: The calcination heating rate is 3°C / min~4°C / min.

6. The method for activated calcination of coal gangue according to claim 1, characterized in that: The reaction time of the gangue clinker immersed in sulfuric acid is 2 to 3 hours.

7. The method for activated calcination of coal gangue according to claim 1, characterized in that: The stirring speed is 120 rpm to 150 rpm, and the stirring time is 3 hours to 5 hours.

8. The method for activated calcination of coal gangue according to claim 1, characterized in that: The mass fraction of the sodium hydroxide solution is 35% to 40%, and the mass concentration of sulfuric acid is 1.84 g / mL.

9. The method for activated calcination of coal gangue according to claim 1, characterized in that: The pretreatment method of coal gangue is to crush the coal gangue, pass it through a 20-40 mesh sieve, and then dry it.

Citation Information

Patent Citations

  • Coal gangue activating and calcining method

    CN113045227A